Coronary arterial geometry: A comprehensive comparison of two imaging modalities. (18th February 2021) - Blanco, Pablo J.; Bulant, Carlos A.; Bezerra, Cristiano G.; Maso Talou, Gonzalo D.; Pinton, Fabio A.; Ziemer, Paulo G. P.; Feijóo, Raúl A.; García‐García, Héctor M.; Lemos, Pedro A.
Abstract: The characterization of vascular geometry is a fundamental step towards the correct interpretation of coronary artery disease. In this work, we report a comprehensive comparison of the geometry featured by coronary vessels as obtained from coronary computed tomography angiography (CCTA) and the combination of intravascular ultrasound (IVUS) with bi‐plane angiography (AX) modalities. We analyzed 34 vessels from 28 patients with coronary disease, which were deferred to CCTA and IVUS procedures. We discuss agreement and discrepancies between several geometric indexes extracted from vascular geometries. Such an analysis allows us to understand to which extent the coronary vascular geometry can be reliable in the interpretation of geometric risk factors, and as a surrogate to characterize coronary artery disease. Abstract : We report a holistic comparison of coronary geometry from CCTA IVUS‐Ax imaging modalities for 34 vessels from 28 patients with coronary disease, discussing agreement and discrepancies between conventional and non‐conventional geometric indexes. We identified two groups of geometric indexes: one group featured a strong correlation between the CCTA and IVUS models; the other group rendered dissimilar finer‐scale characteristics.